Analisis Pengaruh Rasio Keuagan Dalam Memprediksi Perubahan Laba Rugi Di Masa Mendatang - Dharma, Budi; Pratama Tarigan, Mhd Agung; Utami, Annisa Dwi (Jurnal Manajemen Akuntansi (JUMSI), 2022)
To determine a company's growth, financial ratios are one type of analysis that must be performed. For a specific time period, the data from the financial statements include this ratio. When choosing a policy, a company's management can also use financial ratios to anticipate financial decision-making mistakes. Ratio analysis is a method for calculating and measuring financial metrics to assess a company's performance and position.Therefore, the analyst must be able to reconcile the existing factors in this period or time with future factors that may affect the financial condition or performance of the company concerned. Financial ratio analysis clearly provides many benefits for you in managing your business or company. The data obtained after carrying out a financial ratio analysis will give you an idea of how well your business plan is being executed.